Preparation for football competition at moderate to high altitude - Gore, G. J.; McSharry, P. E.; Hewitt, A. J.; Saunders, P. U. (Scandinavian Journal of Medicine & Science in Sports, 2008)
Analysis of ~100 years of home-and-away South American World Cup matches illustrate that football competition at moderate/high altitude (>2000 m) favors the home team, although this is more than compensated by the likelihood of sea-level teams winning at home against the same opponents who have descended from altitude. Nevertheless, the home team advantage at altitudes above ~2000 m may reflect that traditionally, teams from sea level or low altitude have not spent 1-2 weeks acclimatizing at altitude. Despite large differences between individuals, in the first few days at high altitude (e.g. La Paz, 3600 m) some players experience symptoms of acute mountain sickness (AMS) such as headache and disrupted sleep, and their maximum aerobic power (VO2max) is ~25% reduced while their ventilation, heart rate and blood lactate during submaximal exercise are elevated. Simulated altitude for a few weeks before competition at altitude can be used to attain partial ventilatory acclimation and ameliorated symptoms of AMS. The variety of simulated altitude exposures usually created with enriched nitrogen mixtures of air include resting or exercising for a few hours per day or sleeping ~8 h/night in hypoxia. Preparation for competition at moderate/high altitude by training at altitude is probably superior to simulated exposure; however, the optimal duration at moderate/high altitude is unclear. Preparing for 1-2 weeks at moderate/high altitude is a reasonable compromise between the benefits associated with overcoming AMS and partial restoration of VO2max vs the likelihood of detraining.